The Path to Funding The Artist’s Guide to Building Your Audience, Generating Income, and Realizing Career Sustainability - Forshee, Zane; Manceor, Christina; McGinness, Robin (Open textbook library., 2022)
Based on coursework developed at Peabody Conservatory, this book breaks down the process of developing an artist mission statement, generating new ideas for creative projects, and creating an engaging project description. It also covers methods for artists to identify their audience, generate a comprehensive project budget, collect compelling work samples, and identify potential funders to support their creative work. Written by a team of active artists and educators, this resource provides creatives with tools and strategies to communicate passionately and effectively about their work and take control of their financial and artistic future.